Verbalization of indifference through Ukrainian phraseology in modern media discourse - Kniaz, Tetyana (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article identifies the features of the functioning of phraseological units (PhUs) denoting indifference in modern media discourse. Emotionalization is widespread in the media, where emotions are one of the most important ways of influencing the recipient. It is found that the author’s position as a representative of the communicative strategy deserves special attention in covering current issues and reflecting emotional and evaluative attitudes. It is proven that phraseological units with the meaning of indifference reflect the communicator’s attitude to specific events, facts, or a person who feels the emotion of indifference. Modern media discourse testifies to the authors’ resort to structural and semantic changes of usual phraseological units denoting indifference to express a different truth relevant to contemporary realities and events. Analysis of the material shows that the most frequent methods of structural changes are substitution and contamination. Semantic transformations become a continuation of structural changes in phraseological units. The evaluative element of pejorative meaning, explicitly/implicitly reflected in the word components of the analyzed phraseological units, proves that the concept of indifference belongs to the negative zone of the axiological scale. The analyzed PhUs with the meaning of indifference as a forming factor of the media text implement several intentions: informational, nominative, compositional, expressive, and emotional-evaluative. Slang phraseological units in media texts activate the expressive function, and accordingly, the communicative and pragmatic effect of the publication is enhanced. Phraseological units determine communicative strategies regarding the indifferent attitude of an individual or society towards individuals and socio-political situations and reflect the communicative strategy of forming a negative image of selfish individuals with prevailing financial interests. The transformation of a phraseological unit ’My house is at the edge – I will meet the enemy first’ (моя хата скраю – першим ворога зустрічаю) in the media text determines the communicative strategy of forming a positive image of Ukrainians. We see the research prospects in further studying the transformational potential of phraseological units of other thematic groups and their implementations in media discourse.